Performance investigation of installed Pico-Hydro power using maximum power point tracking based on incremental conductance algorithm in solar water pumped storage system - Akhiriyanto, Novan; Waskito A, Wasis; Pratama, Akbar; Satria P, Radith (Politeknik Negeri Lhokseumawe, 2023)
The Solar Water Pumped Storage System (SWPS) has been gaining popularity as an environmentally friendly and sustainable solution to address water supply challenges in areas with abundant solar radiation. The potential energy stored in SWPS is harnessed by converting it into electrical energy through the installed pico-hydro power (picoHP) within the SWPS distribution pipe system. PicoHP performance depended on the flow rate and water pressure, which could not be naturally controlled, leading to low reliability in picoHP generation. This research aimed to optimize picoHP performance through engineering changes in pipe diameter and voltage regulation using a SEPIC MPPT circuit based on the Incremental Conductance (INC) algorithm. The parameters affecting the voltage and current of the picoHP were the water level in the tank and the choice of pipe adapter type based on changes in pipe diameter. The SEPIC MPPT circuit with the INC algorithm began operating when the input voltage from the picoHP reached 7.56 V, resulting in an output voltage of 11.2 V with a duty cycle (D) = 25%. This indicated a delay in the operation of the SEPIC MPPT with the INC algorithm due to the computational process, which did not respond quickly when the input voltage from the picoHP started to decrease. The electrical energy generated by the picoHP through the SEPIC MPPT circuit successfully charged the battery through the BMS module.